Performance of TPS Lines under Raised and Brick Bed Nursery Methods for Tuberlet Production in North Central India - Sadawarti, Murlidhar; Samadhiya, R. K.; Kumar, Shambhu; Singh, S. P.; Roy, Satyajit; Chakrabarti, S. K. (Indian Journal of Hill Farming, 2019)
An experiment was conducted at ICAR-Central Potato Research Station, Gwalior during 2013-14, 2014-15 and 2016-17 with two TPS lines D-150 (Open pollinated) and 92-PT-27 (cross pollinated) and planted in two types of nursery beds viz. brick bed method and normal nursery method in 1.0 m length and 1.0 m breadth (area of 1sq.m). Overall vigour (1-5 scale) was higher in normal method (4.6) over brick bed method (3.6) of planting. Uniformity (1-5 scale) of tubers was at par in both the TPS lines and nursery raising methods. Mean number of tubers (000/m2) was higher in brick bed method (2.94) thannormal method (1.50). Open pollinated family D-150 (2.53) recorded higher number (000/m2) of tubers over cross pollinated family 92-PT-27 (1.89). Weight of tubers (Kg)/m2 was higher in normal method (4.58) than brick bed method (3.84). Among TPS lines tubers yield (Kg/m2) was higher in open pollinated family D-150 (5.11) over cross pollinated family 92-PT-27 (3.30). Hence among the TPS lines D-150 performed better in both the method of planting than 92-PT-27. For production of higher number of tuber using brick bed method was found to be better as far as of nursery raising is concerned. Brick-bed method can be effective for the areas like North-Central India where proper irrigational facilities are the constraints for potato production.